Corporate social responsibility, internal control, and firm financial performance - Zhang, Li; Su, Wunhong (Frontiers in Psychology, 2023)
As the global challenges facing sustainability issues continue to expand, the issues of corporate social responsibility (CSR) and ethical governance have become the focus of continued academic attention. CSR is important for firms to enhance their reputation and promote sustainable development. Using A-share listed firms from 2012 to 2019, this study empirically investigates the effect of CSR fulfillment on internal control and firm financial performance by constructing a regression model. The results show that there is a positive relationship between CSR and firm financial performance. Therefore, CSR fulfillment effectively improves the firm financial performance. Furthermore, this study finds that there is a partial mediating effect of internal control between CSR fulfillment and firm financial performance. Therefore, good internal control leads the firm to implement CSR, strengthen management, and improve financial performance. Further results show that the nature of ownership plays a moderating role in the mediating effect of internal control. This study enriches the mechanism of CSR on firm financial performance. Furthermore, it provides a theoretical basis for Chinese listed firms to fulfill CSR, improve ownership, and strengthen internal control.